2015
DOI: 10.15640/jpesm.v2n1a1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a 6-Week Dry Land Exercise Program for High School Swimmers

Abstract: Background: In swimmers, the great number of stroke repetitions and force generated through the upper extremity, leaves the shoulder uniquely vulnerable to injury. Numerous high school swimmers experience shoulder pain, muscle shortening, and/or weakness leading to poor swim mechanics. Purpose: The purposes of this study were to examine the effects of a six week dry land intervention program on the 1) flexibility of the shoulder girdle, 2) muscular strength of the shoulder girdle and core, and 3) swim performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 39 publications
2
13
0
1
Order By: Relevance
“…In competitive swimming, the propulsive forces responsible for the total body displacement are produced mainly by the upper limbs through the arm adduction and shoulder internal rotation [2]. As such, the swimmers are classified as overhead athletes [3] because high levels of stress are installed in the upper body sections.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In competitive swimming, the propulsive forces responsible for the total body displacement are produced mainly by the upper limbs through the arm adduction and shoulder internal rotation [2]. As such, the swimmers are classified as overhead athletes [3] because high levels of stress are installed in the upper body sections.…”
Section: Introductionmentioning
confidence: 99%
“…Shoulder strengthening programs are part of the training season and require detailed planning [3,7]. Evidence suggests that dryland workouts must be maintained throughout the entire sports season, otherwise the effects of detraining are felt [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Jenna Sawdon-bea observed that 6weeks of dry-land exercise training was helpful for improving core strength but there was not superior shoulder strength and swimming performance. 30 The reason behind the improvement in stroke rate and kicking performance can be because of strength training there was an increase in muscle force of slow and fast twitch muscle fibers that lead to improvement in strength and produce maximal and explosive forces are required for swimming performance.…”
Section: Discussionmentioning
confidence: 99%
“…Após esse período, fez-se uma comparação pré e pós dos grupos. Os testes revelaram uma melhora significativa na força central no grupo de intervenção e que um programa de exercícios em terra seca de seis semanas foi eficaz na melhora da força central (SAWDON-BEA; BENSON, 2015).…”
Section: Ramos Et Alunclassified